Pontos de vista e responsabilidade enunciativa em relatórios técnicos de procedimentos restaurativos no Ministério Público do estado do Rio Grande do Norte - Queiroz, Nouraide Fernandes Rocha de (2020)
This research aims to identify, describe, analyze and interpret the phenomena, Text Plan, Point of View (PDV) and Enunciative Commitment (EC), in Technical Restorative Procedure Reports. It deals with the discursive genre circumscribed in the domain of legal discourse, within the Public Ministry of the State of Rio Grande do Norte (PMRN). The corpus comprises 19 (nineteen) Reports that refer to conflicts in the realm of community, school and/or family relations, which implicate the applicability of restorative practices, solicited by the District Attorney’s Juvenile Justice department, seeking conciliatory solutions to these conflicts. The research relies on the theoretical support of Textual Discourse Analysis (TDA), proposed by Adam (2011), based on Textual Linguistics (TL) and Enuniciative Linguistics (EL). The research describes the compositional structure of the Reports, its text plan, and seeks to analyze linguistic strategies that indicate the assumption or not of the EC, by the first speaker/enunciator (S1/E1), or rather, by the facilitators of the restorative practices. Thus, studies by Rabatel (2003, 2009, 2010, 2016, 2017, 2018) are also highlighted, with respect to POV and EC. The enunciative approach, with its foundation in theories of polyphony and dialogic discourse make it possible to investigate EC taking into account the different types of representations of speech embedded in the transmission of the discourse and in the role the speaker plays, on attributing it to some other speaker or assuming responsibility for the propositional content of his/her own speech. To investigate the mediating frameworks, the theoretical basis is drawn from Guentchéva (1990, 1993, 1994, 1996, 2011, 2014) who analyzes the gramatical category of mediativity (MED) from the linguistic marks, which allows for the identification of the engagement or distancing of the speaker in relation to the propositional content of the utterances. Studies by Rodrigues, Passeggi and Silva Neto (2014), Rodrigues (2016a, 2016b, 2017, 2018), Rodrigues e Passeggi (2016), Lourenço (2008, 2015, 2018), among others are focused on the approaches to analyzing legal discourse. To achieve the aims of the proposed study, in this thesis two categories of analysis were chosen: the different types of representation of speech and the indications of the mediating frameworks that characterize, in textual materiality, the degree of EC in propositional enunciations. In this sense, the methodology can be characterized as qualitative, bibliographic and documentational, interpretivist in nature, and using the inductive method. the analysis of the corpus allowed us to identify a conventional text plan. The analysis of the points of view, according to the rabatelian assumptions, shows us the preponderance of a represented PDS, with recurrence of narrated and asserted PDS. In this sense, we find that L1 / E1 sometimes attributes RE to e2, and at other times it explicitly assumes it in a specific way in the textual zone for closing the Reports. We also identified the occurrence of a mediative framework, introduced by conformative connectors and by discendi verbs.